خانوادہ عثمانیہ (بدایوں)کے علما و مشاہیر اور ان کی تالیفات: ایک مطالعہ: A Study of the Scholars of the Ottoman family (Badāyūn) and their Writings (Al-Qamar, 2020)
Scholars of Khānwādah ʻUthmāniah (Badāyūn) have authored a large number of important books on different topics including literature, tafsīr, Ḥadīth, scholastic theology etc. Among those leading scholars, Syed Al-e--Ahmed Achay Miān, Fazal Rasūl Badāyūnī, Abdul Qādir Badāyūnī, Abdul Muqtadir Qādrī, Syed Abu al-Hussain Ahmed Noorī, Muhammad Mohy-ud-dīn Qādrī, Hakeem Abdul Qayyūm Shaheed Qādrī, Abdul Mājid Badāyūnī, Abdul Hamīd Badāyūnī, Muhammad Abdul Hādī Qādrī and Usaid-ul-Haq Muhammad ʻAsim Qādrī are noteworthy. Badāyūn’s Compilations of these scholars are simple, literary, readable and a milestone in the advancement of religious knowledge.
Keywords: Khānwādah ʻUthmāniah; Badāyūn; writings